The effects of a home visit‐supported nursing education program on certain parameters in older adults living alone at home - Arabacı, Zeynep; Kaçan, Havva (Wiley, 2024)
AbstractBackgroundThe rapid aging of the world population is emerging as a global public health issue, and the likelihood of living alone increases with age.AimThis study aims to develop healthy lifestyle behaviors, reduce loneliness levels, and increase social support capacity among older adults living alone at home.Research modelThe present study was designed as a quasi‐experimental study.MethodThis study included 49 older adults aged 65 and above who agreed to participate, with 26 in the experimental group and 23 in the control group. The data collection tools used were the Introductory Information Form, the healthy lifestyle behavior scale II, the UCLA loneliness scale Short Form‐6, and the multidimensional scale of Perceived Social Support. The experimental group received individualized nursing education programs through weekly 60‐min home visits for 8 weeks. The study followed the CONSORT flow diagram.ResultsThe results indicate a statistically significant difference between the pretest and posttest scores of the experimental group in the “Friend” dimension of the Perceived Social Support Scale. However, no difference was found in the healthy lifestyle behavior scores and the loneliness scale scores.ConclusionIt is difficult to achieve significant improvements in short periods among older adult groups. Substantial changes may not have occurred because this study included pretest and posttest measures over an 8‐week period. Therefore, future studies should consider longer durations and include follow‐up processes to observe more significant effects.Implications for nursing practiceIt is anticipated that there will be a successful aging process in studies supported by long‐term home visits by nurses.